AKULTURASI BUDAYA UMAT HINDU ETNIS JAWA DAN BALI DI WILAYAH KECAMATAN TOILI KABUPATEN BANGGAI SULAWESI TENGAH - Sugiarti (Widya Aksara, 2019)
Hinduism spread throughout the Indonesian archipelago, and is embraced by various tribes and ethnicities in Indonesia. Therefore, Hinduism has a different religious culture between one place and another, between ethnic groups and ethnic groups and other ethnic groups. This makes the Hindu religious culture diverse, distinctive, and regionally characteristic, according to where the tradition was born. But also not infrequently, these cultural actors seek a middle ground by doing acculturation. This method is considered effective in uniting the differences brought by each tribe or ethnicity. Acculturation that occurs does not eliminate the original cultural elements of the ethnic group or ethnicity concerned, but instead produces a new culture that is equally acceptable to both, and is considered in accordance with the social environment in which the two communities live.